'Back to Africa': increased taxon sampling confirms a problematic Australia‐to‐Africa bee dispersal event in the Eocene. (12th June 2017) - KAYAALP, PELIN; STEVENS, MARK I.; SCHWARZ, MICHAEL P.
Abstract: Colletidae is a predominantly southern hemisphere bee family with a Late Cretaceous origin and with an inferred ancestral region covering late Gondwanan South America, Antarctica and Australia. One highly diverse colletid subfamily, Euryglossinae, is entirely restricted to Australia and the strictly Afrotropical subfamily Scrapterinae has been inferred as its sister clade. This has led to suggestions that Scrapterinae represents a highly unusual post‐Gondwanan dispersal from Australia to Africa, but phylogenetic studies to date have included only minimal representatives from each subfamily. Here we greatly increase the level of species sampling of both subfamilies and develop a molecular phylogeny based on one mitochondrial and two nuclear genes. Our results indicate that the broad results of earlier studies are robust to substantially greater taxon sampling, and we infer a divergence date between the two subfamilies in the early Eocene. Dispersal pathways between Africa and Australia during that time are problematic, with several studies suggesting dispersals via the now largely submerged Kerguelen and Crozet Plateaus. Our results contribute another example of a puzzling sister‐clade relationship between African and Australian taxa and indicate the need to better understand southern hemisphere subaerial configurations, including Antarctica, and ocean and wind currents at those times. Abstract : We support the inferred sister‐clade relationship between the highly diverse colletid Australian subfamily Euryglossinae and the Afrotropical subfamily Scrapterinae. We show that broad results of earlier studies are robust to substantially greater taxon sampling, and we infer a divergence date between the two subfamilies in the early Eocene. This study is another example of a puzzling sister‐clade relationship between Africa and Australia dating to the Eocene and indicates the need to understand southern hemisphere subaerial configurations, including Antarctica.